Energy-Level Spacing Distribution of Quantum Systems via Conformable Operators - Hern'andez-G'omez, Juan C.; Vald'es, Juan E. N'apoles; Rosario-Cayetano, Omar; Fleitas, Alberto (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper we introduce a Gaussian-like function, as a solution of a Conformable Differential Equation (CDE) of order 0